1970
DOI: 10.1161/01.res.26.5.583
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Vibration Distal to Stenoses in Isolated Arteries of Dog and Man

Abstract: It has been suggested that poststenotic weakening of arterial walls is caused by arterial wall vibration and structural fatigue initiated by pressure disturbances in turbulent blood flow. We examined the frequency spectra of wall vibration downstream from experimental arterial stenoses and compared them with the natural resonant vibration characteristics of the artery walls. Spectra of arterial wall displacement of isolated perfused dog and human arteries were measured with a noncontacting capacitanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

1972
1972
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 11 publications
4
21
0
Order By: Relevance
“…5 The damaging effect of the vibration has been shown to increase when the vibrations occur at the resonant frequencies of the arterial wall. 6 Advanced methods of acoustic spectral analysis can be used to examine the complicated dynamic system influencing vascular flow within and distal to the saccular aneurysms.Research involving sound emission and acoustic spectral analysis to examine flow properties and aneurysmal pathophysiology was initiated by intraoperative observations of clear aneurysmal sounds distinct from the sound of parent vessels and by reports of cranial bruits detectable with a clinical stethoscope in a small percentage of patients with saccular aneu- Received July 11, 1989; accepted April 4, 1990. rysms. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 The damaging effect of the vibration has been shown to increase when the vibrations occur at the resonant frequencies of the arterial wall. 6 Advanced methods of acoustic spectral analysis can be used to examine the complicated dynamic system influencing vascular flow within and distal to the saccular aneurysms.Research involving sound emission and acoustic spectral analysis to examine flow properties and aneurysmal pathophysiology was initiated by intraoperative observations of clear aneurysmal sounds distinct from the sound of parent vessels and by reports of cranial bruits detectable with a clinical stethoscope in a small percentage of patients with saccular aneu- Received July 11, 1989; accepted April 4, 1990. rysms. …”
mentioning
confidence: 99%
“…5 The damaging effect of the vibration has been shown to increase when the vibrations occur at the resonant frequencies of the arterial wall. 6 Advanced methods of acoustic spectral analysis can be used to examine the complicated dynamic system influencing vascular flow within and distal to the saccular aneurysms.…”
mentioning
confidence: 99%
“…This is where the turbulent jet from the stenosis may be expected to impinge on the arterial wall 10 and is the region where post-stenotic dilatation occurs. Roach and colleagues 6 ' 13 have shown that isolated segments of arteries subjected to various external frequency vibrations become more distensible.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another factor is the presence, degree, and location of arterial stenosis that can excite vibrations with the specific frequencies dependent on the nature of the arterial wall. 32 Arterial vibration can produce damage to and reductions in the function of the elastin component of the arterial wall. 33,34 Vibration can cause damage in vascular endothelial cells 35 and produce endothelial cell dysfunction.…”
Section: Vibrations Originating From Arteriesmentioning
confidence: 99%